(untitled) (Ghana Journal of Science, Technology and Development, 2020)
Access to climate information is one of the ways by which farmers can reduce the adverse effects of climate variability and change. However, in Ghana, and in particular, Northern Ghana there is a gap between meteorological information and farming activities. This paper examined farmersâ€™ willingness-to-pay for weather forecasts provided through mobile phone messaging. A total of 391 respondents, selected through a multi-stage sampling procedure was used. Based on the contingent valuation framework, a double-hurdle model was estimated. On average, a farmer was willing to pay GHâ‚µ 122.15 annually for weather forecasts in the form of a text message. The results of the selection equation of the double-hurdle model show that sex, education, production aim, adaptive capacity and climate information source were significant and positively influenced willingness to pay for weather forecast while age and credit access negatively influenced same. Similarly, while dependency, extension service and adaptive capacity were significant and positively influenced the amounts farmers were willing to pay, sex and climate information access, negatively influenced the same. It is concluded that although the willingness-to-pay for weather forecast is low, especially, among male farmers, there exists a market for weather forecast that can be harnessed by the meteorological agencies. Some of the categories of farmers that may be targeted for demand and policy formulation are the following: farmers with formal education; farmers with access to extension services; market-oriented farmers; and farmers with adaptive capacity to climate change.